Experimental Study of Constant Volume Sulfur Dust Explosions - Joseph Kalman; Nick G. Glumac; Herman Krier (Journal of Combustion)
Dust flames have been studied for decades because of their importance in industrial safety and accident prevention. Recently, dust flames have become a promising candidate to counter biological warfare. Sulfur in particular is one of the elements that is of interest, but sulfur dust flames are not well understood. Flame temperature and flame speed were measured for sulfur flames with particle concentrations of 280 and 560 g/m3 and oxygen concentration between 10% and 42% by volume. The flame temperature increased with oxygen concentration from approximately 900 K for the 10% oxygen cases to temperatures exceeding 2000 K under oxygen enriched conditions. The temperature was also observed to increase slightly with particle concentration. The flame speed was observed to increase from approximately 10 cm/s with 10% oxygen to 57 and 81 cm/s with 42% oxygen for the 280 and 560 g/m3 cases, respectively. A scaling analysis determined that flames burning in 21% and 42% oxygen are diffusion limited. Finally, it was determined that pressure-time data may likely be used to measure flame speed in constant volume dust explosions.